MULTIMEDIA INTERAKTIF BERBASIS KONFLIK KOGNITIF MENGGUNAKAN SMARTPHONE PADA MATERI KARAKTERISTIK GELOMBANG MEKANIK - Indriyani, Ririn; Mufit, Fatni (Program Studi Pendidikan Fisika FKIP Universitas Jambi, 2023)
Almost all students already have a smartphone, but it has not been maximally used for media of learning. This problem was to develop interactive multimedia based on the conflict of cognitive using a smartphone. The study's purpose was to describe the characteristics and produce multimedia of interactive based on a conflict of cognitive that was valid on the material of mechanical wave characteristics. The research conducted was a research of development using the Plomp model. The research procedure consists of preliminary research and development/prototyping phases. This limited research was in the expert review stage. The data collection instruments from this study were the educator's questionnaire sheet, the literature study sheet, the self-evaluation questionnaire sheet, and the validity test sheet. The data analysis techniques used were the percentage technique and the V Aiken technique. In the Develop / Prototyping Phase, interactive multimedia has been designed based on the syntax of the conflict of the cognitive model in learning. The self-evaluation result was obtained with very valid criteria. The validity result of the test obtained an average of 0.77 with a valid category. Therefore, multimedia of interactive based on the conflict of cognitive on mechanical wave characteristics material has been valid in terms of the substance of the material, design of learning, display of visual communication, and utilization of software.